Prototipo de máquina lavadora y peladora de papa en el departamento de Nariño (2022)
This project describes the process of conceptual design, selection of elements and construction of a potato washing and peeling machine prototype. The prototype seeks to reduce the demand for effort, water consumption and potato waste for use by restaurants and fast food chains in the department of Nariño. The Design Thinking methodology will be used to propose a low cost, user centered solution that reduces process time and avoids wasting raw materials quickly and efficiently.